The impact of regulation on the seasoned equity offering decision. Issue 1 (February 2020) - Melia, Adrian; Docherty, Paul; Easton, Steve
The rarity of rights issues in the United States makes it difficult to examine the choice between alternative seasoned equity offering (SEO) methods in that market. In Australia, however, both rights issues and private placements are prevalent. We therefore use the Australian market to test whether regulation influences a firm's choice between rights issues and private placements. When a firm decides to issue seasoned equity in Australia, regulation favours private placements if the issue is small or needs to be completed quickly. Consistent with regulations affecting the choice between SEO types, our empirical results provide evidence that firms in Australia are more likely to choose a private placement for small issues or when taking advantage of temporary periods of overvaluation. JEL Classification:G12, G14